Evaluasi Sertifikasi Green Building pada Gedung Institut Teknologi & Sains Bandung - Siti Mega Rosalia; Annisa Annisa; Siswanti Zuraida (Institut Teknologi Sains Bandung, 2020)
Global warming is one of the world’s prominent issue that related to the environment. As a support to reduce the causes of global warming, Institut Teknologi dan Sains Bandung (ITSB) has applied a concept of green building and got the greenship building’s certificate since 2013 2016 with the result score was 64 points or gold category of Green Building of Council Indonesia (GBCI). This study aims at evaluating the existing building of ITSB for knowing the new result score of greenship building’s certification. This results score can be a simple directive for ITSB to do the new certification. The collecting data that used were partisipative observation, interview, and quisionnaire as the primary data and literature as the secondary data. The evaluative-descriptive qualitative methods was used to analyze data. The evaluating of Greeship Existing Buildings using an assessment from GBCI with 6 parameters, those parameters are Approprite Site Developent (ASD), Energy Efficiency and Conservation (EEC), Water Conservation (WAC), Material Resource and Cycle (MRC), Indoor Health and Comfort (IHC) , and Building Environmental Management (BEM). The result of this research show that the accumulation of the scores of 6 parameters were 47 points, it means that ITSB could receive the bronze category on Greenship Existing Building.